Curcumin activates NLRC4, AIM2, and IFI16 inflammasomes and induces pyroptosis by up-regulated ISG3 transcript factor in acute myeloid leukemia cell lines. Issue 1 (31st December 2022) - Zhou, Yuru; Kong, Yunyuan; Jiang, Mei; Kuang, Linju; Wan, Jinhua; Liu, Shuyuan; Zhang, Qian; Yu, Kuai; Li, Na; Le, Aiping; Zhang, Zhanglin
ABSTRACT: Curcumin, the primary bioactive component isolated from turmeric, has been found to possess a variety of biological functions, including anti-leukemia activity. However, the effect of curcumin in different leukemia cells vary. In this study, we demonstrated that curcumin induced the expression of AIM2, IFI16, and NLRC4 inflammasomes in leukemia cells U937 by increasing the expression levels of ISG3 transcription factor complex, which activated caspase 1, promoted cleavage of GSDMD, and induced pyroptosis. We also found that pyroptosis executor GSDMD was not expressed in two curcumin-insensitive cells HL60 and K562 cells. In addition, exogenous overexpression of GSDMD by lentiviral transduction in K562 cells increased the anti-cancer activity of curcumin, and inhibiting the expression of GSDMD by shRNA enhanced U937 cells to resist curcumin. The results showed that inducing pyroptosis is a novel mechanism underlying the anti-leukemia effects of curcumin.